2016
DOI: 10.1212/wnl.0000000000003305
|View full text |Cite
|
Sign up to set email alerts
|

Progression of brain atrophy in PSP and CBS over 6 months and 1 year

Abstract: Objective: To examine the utility and reliability of volumetric MRI in measuring disease progression in the 4 repeat tauopathies, progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS), to support clinical development of new tau-directed therapeutic agents.Methods: Six-and 12-month changes in regional MRI volumes and PSP Rating Scale scores were examined in 55 patients with PSP and 33 patients with CBS (78% amyloid PET negative) compared to 30 normal controls from a multicenter natural history st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 33 publications
7
67
2
Order By: Relevance
“…This finding is consistent with previous studies showing an increased involvement of cortical areas in CBS (5, 38). Accordingly, we observed increased within-network rsFC in the executive-control and insula RSNs.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with previous studies showing an increased involvement of cortical areas in CBS (5, 38). Accordingly, we observed increased within-network rsFC in the executive-control and insula RSNs.…”
Section: Discussionsupporting
confidence: 94%
“…The smaller numbers reported by Whitwell et al 31 may result from the fact that they only included patients with a clinical diagnosis of probable PSP (NINDS-SPSP criteria), whereas the other studies 6,30 and our study also included patients with possible PSP or modified diagnostic criteria, which may affect the variability in disease progression markers. Finally, a most recent study 8 used SPM12-based longitudinal morphometric analysis and found that the annual change in midbrain volume as outcome measure requires only 56% of patients as the PSPRS. This rate compares well with the 63% observed in our study, which also used SPM12.…”
Section: Discussionmentioning
confidence: 99%
“…placebo and verum) patients from the davunetide trial and concluded that midbrain volumetry as outcome measure in a 1-year parallel-group trial would require comparable numbers of patients 6 as the best performing clinical scale, the PSP-rating scale (PSPRS). 5,7 Another study 8 proposed that annual midbrain volume change measured with SPM12 would require 44% less patients than the PSPRS.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in MRI methodology and statistical testing might explain discrepancies among studies. The previous studies used voxel-based morphometry7 or measured ROI volumes using automated approaches 8 9. It is noteworthy that GM volume changes can result from alterations in two cortical components, cortical thickness and cortical surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive WM volume loss after 1 year in frontal and parietal lobes, brainstem, and cerebellum was observed in patients with PSP-RS using structural MRI 7. To our knowledge, only one longitudinal DT MRI study reported microstructural WM changes over 6 months in SCPs and left inferior frontal WM in patients with PSP-RS 19.…”
Section: Introductionmentioning
confidence: 87%